Ansaẗze fur̈ ein produktspezifisches Marketing fur̈ Ok̈o-Produkte im konventionellen Handel - eine Verbraucheranalyse im Elbetal - Antje Wirthgen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Approaches for Product-specific Retail Marketing for Organic Food - A Consumer Survey in the Elbe-Valley Against the background of increasing political importance of organic farming combined with market potential for organic food, especially concerning conventional retailers, this article aims to improve organic marketing for retailers by means of product-specific analysis of consumers purchase behaviour. The main research aspects based on a consumer survey are preference testing and attitude measuring to explain consumers purchase behaviour concerning selected products. The preference test furthermore offered the possibility to examine the impact of substitutes produced by other environmentally friendly production methods and to estimate the market potential for organic food. The findings of this research are firstly hints on market potential for organic food considering the competitive situation under price impact and secondly product specific approaches to improve retail marketing for organic food, in order to facilitate to tap the market potential. These are for instance product-specific price differentiation and the reduction of consumers insecurity against some environmentally friendly ways of production especially with regard to growing grains or animal husbandry.
Keywords: 330; Öko-Produkt; Marketing; Konsumentenverhalten; Conjoint-Analyse